Artificial Neural Network: Understanding the Basic Concepts without Mathematics - Han, Su-Hyun; Kim, Ko Woon; Kim, SangYun; Youn, Young Chul (Dementia and neurocognitive disorders, 2018)
Machine learning is where a machine (i.e., computer) determines for itself how input data is processed and predicts outcomes when provided with new data. An artificial neural network is a machine learning algorithm based on the concept of a human neuron. The purpose of this review is to explain the fundamental concepts of artificial neural networks.